Inorganic additive-incorporated composites with infrared radiation performance for thermal management - Wu, Yingsi (2023)
Purpose: Personal thermal management in functional textiles is in increasing demand for health care, outdoor activity and energy saving. Thus, developing new strategies is highly desired for radiative cooling and/or heating by manipulation of the transmissivity, reflectivity and absorptivity of the textiles within solar energy and human body heat radiation ranges. Design/methodology/approach: Inorganic additives including TiO2, Fe2O3, carbon black (CB), graphene and mica were incorporated into polymer films. The inorganic additives' full spectrum properties and thermal responses were comprehensively investigated. Findings: The CB composite film showed the highest absorptivity over the full solar to human body radiation spectrum. The mica-white (mica-w) (mica coated with TiO2) and mica-red (mica-r) (mica coated with Fe2O3) composites showed the lowest solar energy absorptivity and a strong body heat radiation reflectivity. Furthermore, according to composites' thermal responses to the simulated solar and human body radiations, CB and mica are promising for both cooling and heating when applied in dual-functional thermal management textiles. Research limitations/implications: Research has limitation related the amount of additives which can be added to textile. When powder is added to polyester yarn, the amount is limited by 2–3%. When powder is added to the composite which is used for printing, the amount of powder is limited by 5%. Practical implications: A lot of apparel, especially sport apparel, contains prints. Decoration is one part of print application. Now, a lot of companies work under development of different additives, which provide additional properties to apparel. The closest targets for powder added to prints are cooling and heat retention. Quite often, inorganic additives possess dual properties: the inorganic additives may be heat reflective which his needed for heat retention, but may have high-thermal conductivity, which works well for cooling. Human body has complicated mechanism of heat exchange: convection, radiation and moisture evaporations play main role. The same additive may be cooling if there is a contact with skin but may be heating (IR reflective) if placed in the second or third layer. Thus, effect is needed to be studied first before real application. Originality/value: This work could provide a comprehensive guideline for the rational design and application of thermal management composite textile materials by revealing the full solar to human body radiation performance of a series of inorganic materials.